Strategies and tricks of candidate leaders during elections in Islam - Anggraeni, Intan Cahya; Maspupah, Neng; Herdiati, Rifa Diani (Research in Education and Technology (REGY), 2024)
This research aimed to analyze the strategies and tricks of candidate leaders in the election. The research method used descriptive-qualitative where this research interpreted the management of candidate leaders during the election. This research used a descriptive analysis method where the research looked at a case that leads to a problem in physical or structural form (real or unreal). Candidate leaders carried out various strategies and tricks. The strategies and tricks of candidate leaders in Indonesia usually involve socializing work programs and approaching the community to gain public sympathy. The requirements and criteria that must be met in leading Indonesia are Indonesian citizens, religious, of sufficient age, honest, fair, trustworthy, caring for others, free from a history of problems (cases), and healthy (no history of illness).